ASEAN's Reaction To Forced Labor Exploitation in the Fishing Sector in Indonesian Waters - Desy Syamsurini Ekawati (Dinasti Publisher, 2024)
This paper aims to analyze ASEAN's role in addressing forced labor exploitation in the fisheries industry in Indonesia through the ASEAN Ministerial Meeting in Transnational Crime (AMMTC) framework. The exploitation of workers in fisheries has emerged as a problem in the fisheries and seafood industry in Indonesia, although several international conventions have been made and ratified, its handling is complicated by the challenges of vested interests. The seafood supply chain is one of complex global value and involves a variety of sources including the use of workers who are vulnerable to deception and coercion in their recruitment and employment. The role of ASEAN as a regional organization is very influential in solving this problem and it requires compact cooperation between international organizations and governments to jointly handle it. This research raises the question “Why has the ASEAN cooperation mechanism not been able to reduce the level of exploitation of ship workers in Indonesian waters?”. To find out and explain the research question, the concept of international organization will be used.